A merry Murdoch Christmas [videorecording (DVD)] - Bisson, Yannick, 1969-; Craig, Tom, 1962-; Joy, Hélène (Murdoch mysteries., 2016)
The two-hour Christmas special, has Murdoch and the team investigating the host of a Christmas charity gala for sick children after he is killed, and all the presents he was going to give away are stolen. When witnesses report hearing a wild animal near the scene, Crabtree suspects the legendary creature Krampus is the culprit.